BRD3‐NUTM1‐expressing NUT carcinoma of lung on endobronchial ultrasound‐guided transbronchial needle aspiration cytology, a diagnostic pitfall. Issue 2 (21st October 2021) - Aryal, Sameer Chhetri; Zia, Shereen; Rodgers, Shannon; Shen, Yulei; Perry, Kyle; Yuan, Lisi
Abstract: Background: Nuclear protein in testis (NUT) carcinoma (NC) is an aggressive type of poorly differentiated carcinoma with a variable degree of squamous differentiation. NC is defined by the presence of BRD‐NUT fusion oncogenes, the most common fusion form being the BRD4‐NUTM1 gene. Variant rearrangements involving the BRD3 and NSD3 genes. Variant rearrangements involving the BRD3 and NSD3 genes occur in approximately one‐third of the cases. Aims: This is the first case regarding the study of cytological features of NC of the lung with BRD3‐NUTM1 fusion. Materials and Methods: A 36‐year‐old female with chest heaviness and shortness of breath was found to have a right‐sided pleural effusion; she was non‐smoker and denied any significant past medical illness. CT‐chest revealed an 8.5 cm heterogeneous mass in the right and mid‐upper lung. She underwent endobronchial ultrasound‐guided (EBUS) transbronchial fine‐needle aspiration (FNA) of the lung mass. Thoracocentesis was performed, and pleural fluid was sent to the laboratory for cytological evaluation Results: The cytopathological findings showed atypical squamoid cells with variably prominent single or multiple nucleoli. Monotonous‐looking cells with high nuclear to cytoplasmic ratio and hyperchromasia were also present. The atypical squamoid cells showed abundant clear to eosinophilic cytoplasm with rare individual cell keratinization and focal keratin pearl formation. The atypical cells were positive for CK7, p40, p63, mCEA and equivocal for NUT‐specific antibody. The cytopathological findings were consistent with squamous cell carcinoma with focal keratinization. The Fusion Panel‐Solid Tumor (50 genes) revealed BRD3‐NUTM1 fusion gene. Diagnosis was amended to pulmonary NC. Discussion: NC is a diagnostic challenge for pathologists as it can morphologically mimic undifferentiated carcinoma, squamous cell carcinoma, or neuroendocrine carcinoma. The challenge is not how to diagnose NC but rather determining when to include it in the differential diagnosis and perform the diagnostic molecular tests (FISH or NGS) or IHC study for NUT‐specific antibody. Conclusion: When a specimen demonstrates a dual cell population of squamoid cells and primitive‐looking tumor cells in the wrong clinical context (i.e., young patient with no smoking history), further molecular profiling is warranted to include the differential of a primary NC of the lung. The cytological features of NC itself have rarely been documented and moreover, that of a primary NC of the lung with BRD3‐NUTM1 fusion has never been reported. We herein report cytological findings of a primary NC of the lung with BRD3‐NUTM1 fusion gene.